Design and implementation of smart waste recycling bin for the household environment based on IoT. Issue 6 (26th October 2020) - Harjoseputro, Yulius; Julianto, Eddy; Handarkho, Yonathan Dri; Ritonga, Yuriska Indriati Talenta
Abstract : Purpose: This study aims to build a prototype of a smart waste recycling bin to transform organic waste into liquid fertilizer. The internet of things (IoT) was used as a base to develop this bin to offer a recycling system that convenient to the household. Design/methodology/approach: In general, this system will integrate a microcontroller and several sensors that able to be controlled by a smartphone app to manage the decomposition process of organic waste in the bin. In the end, black-box testing was conducted to ensure all hardware and software that construct the system can perform well as expected. Findings: All the validation testing reveals all the integration of hardware and software that constructs the smart bin satisfied the performance requirement except for the real-time clock sensor that implies the slight error for a few seconds compares to the actual time. Originality/value: Different from the previous works, this study focused on the involvement of society to participate in the recycling garbage process by designing the smart waste recycling bin system that fits to locate in the household environment, which allows users to monitor the fertilizer making process using IoT technology.